The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.est.1c06990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Per- and Polyfluorinated Alkyl Substances Present in Commercial Anti-fog Products and Their In Vitro Adipogenic Activity

Abstract: Anti-fog sprays and solutions are used on eyeglasses to minimize the condensation of water vapor, particularly while wearing a mask. Given their water-repellent properties, we sought to characterize per- and polyfluorinated alkyl substance (PFAS) compounds in four anti-fog spray products, five anti-fog cloth products, and two commercial fluorosurfactant formulations suspected to be used in preparing anti-fog products. Fluorotelomer alcohols (FTOHs) and fluorotelomer ethoxylates (FTEOs) were detected in all pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 76 publications
(109 reference statements)
2
25
0
Order By: Relevance
“…However, the component ions created a web of apparent CF 2 - and C 2 H 4 O-homologous series where the number of perfluoroalkyl repeating units remained fixed as the number of ethoxy repeating units varied and vice versa. This suggests the presence of a polyethoxylated PFAS series, which have been previously reported, although with different composition and not in AFFF. Several of the nodes in Figure A are associated with 34 S isotopologues, and none were associated with 37 Cl isotopologues. Because no P-containing formulas were identified in the AFFF sample during suspect screening, molecular formulas were calculated for the series using C 0‑∞ , H 0‑∞ , F 0‑∞ , N 0‑6 , O 0‑∞ , and S 0‑5 as elements and a mass error window of ±0.2 ppm.…”
Section: Resultssupporting
confidence: 63%
“…However, the component ions created a web of apparent CF 2 - and C 2 H 4 O-homologous series where the number of perfluoroalkyl repeating units remained fixed as the number of ethoxy repeating units varied and vice versa. This suggests the presence of a polyethoxylated PFAS series, which have been previously reported, although with different composition and not in AFFF. Several of the nodes in Figure A are associated with 34 S isotopologues, and none were associated with 37 Cl isotopologues. Because no P-containing formulas were identified in the AFFF sample during suspect screening, molecular formulas were calculated for the series using C 0‑∞ , H 0‑∞ , F 0‑∞ , N 0‑6 , O 0‑∞ , and S 0‑5 as elements and a mass error window of ±0.2 ppm.…”
Section: Resultssupporting
confidence: 63%
“…Examples of widespread pre-PFAAs likely relevant for direct human exposure are in the second semicircle ( III : perfluoroalkyl sulfonamides (FASAs); IV : fluorotelomer sulfonates (FTSs); V : polyfluoroalkyl phosphoric acid diesters (diPAPs); VI : perfluoroalkyl sulfonamido acetic acids (FASAAs); VII : fluorotelomer alcohols (FTOHs)). Examples of source-associated pre-PFAAs with poorly understood importance for direct human exposure are shown in the outer circle and include compounds with known or suspected use in consumer products ( VIII, IX, X ) , and structures identified in highly impacted areas (fluorochemical manufacturing site ( XI ) and AFFF source zones ( XII ; XIII ). ).…”
Section: What Makes a Pfas A “Precursor”?mentioning
confidence: 99%
“…A recent study by Herkert et al 18 at Duke’s Nicholas School of the Environment found that anti-fogging sprays and cloths commonly used to prevent fogging on protective eyewear may contain high levels of polyfluorinated alkyl substances. Exposure to these substances has been associated with toxicological effects such as impaired immune function, cancer and thyroid disease.…”
Section: Discussionmentioning
confidence: 99%